Spatial control of doping in conducting polymers enables complementary, conformable, implantable internal ion-gated organic electrochemical transistors - Duncan J. Wisniewski; Liang Ma; Onni J. Rauhala; Claudia Cea; Zifang Zhao; Alexander Ranschaert; Jennifer N. Gelinas; Dion Khodagholy (Nature Communications)
Abstract Complementary transistors are critical for circuits with compatible input/output signal dynamic range and polarity. Organic electronics offer biocompatibility and conformability; however, generation of complementary organic transistors requires introduction of separate materials with inadequate stability and potential for tissue toxicity, limiting their use in biomedical applications. Here, we discovered that introduction of source/drain contact asymmetry enables spatial control of de/doping and creation of single-material complementary organic transistors from a variety of conducting polymers of both carrier types. When integrated with the vertical channel design and internal ion reservoirs of internal ion-gated organic electrochemical transistors, we produced matched complementary IGTs (cIGTs) that formed high-performance conformable amplifiers with 200 V/V uniform gain and 2 MHz bandwidth. These amplifiers showed long-term in vivo stability, and their miniaturized biocompatible design allowed implantation in developing rodents to monitor network maturation. cIGTs expand the use of organic electronics in standard circuit designs and enhance their biomedical potential.